PENGARUH PENAMBAHAN PLASTIK BEKAS TIPE LOW DENSITY POLYETHYLENE (LDPE) TERHADAP KINERJA CAMPURAN BERASPAL - Widi Wantoro; Dyah Kusumaningrum; Bagus Hario Setiadji; Wahyudi Kushardjoko (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2013)
Asphalt mixture performance needs to be improved by modifying the asphalt mixture to produce a strong, durable and high plastic-deformation resistance. While the presence of abundance of plastic waste takes 1000 years to be decomposed perfectly by land. According to the facts,this research was proposed to improve performance of asphalt mixture by utilizing plastic waste. This is because plastic has high softening point so that it is expected to be able to increase asphalt mixture resistance against the effects of temperature and elasticity. The research was done by substituting a part of filler with LDPE plastic waste in asphalt mixture. Different contents of LDPE, i.e. 0%, 2%, 4% and 6% of the weight of asphalt, were used in this study to simulate the effect of plastic content on mixture performance. Fifteen samples of AC-WC mixture were made for each variation of LDPE content and all were compacted by 2x75 blows. Then, the mixtures were evaluated by terms of 6 Marshall properties, that is, stability, flow, MQ, VIM, VMA and VFA, one additional parameter, namely Index residual strength (IRS). It resulted that mixtures with plastic tend to less dense (as showed by higher air voids) and become more rigid (as showed by high stability but low flow). This indicates that the addition of LDPE could make the mixture becoming more rigid but porous causing it has good resistance to plastic deformation but it is more susceptible to cracking and less durable. Although the results showed that mixture with LDPE was not better than conventional mixture, the use of this mixture for underlying layer like AC-BC is still possible. And this is supported by all Marshall properties on selected types (2% and 4%) could fulfil the specification issued by Directorate General of Highway (Bina Marga).